2004
DOI: 10.1080/01443610410001722671
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between transvaginal ultrasound measured endometrial thickness and histopathological findings in Afro-Caribbean Jamaican women with postmenopausal bleeding

Abstract: Postmenopausal bleeding is traditionally investigated with invasive procedures. Recent studies in white populations have suggested that these procedures can be avoided, as ultrasonographic endometrial thickness of < 5 mm is not associated with malignancy. We performed a prospective study in 75 Jamaican Afro-Caribbean women with postmenopausal bleeding to determine whether an endometrial thickness of < 5 mm excluded endometrial cancer. We also examined the aetiology of postmenopausal bleeding and looked for pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 10 publications
2
21
2
Order By: Relevance
“…5,6 In our study, the presence of LN metastasis was associated significantly with the patient's age. Savelli et al reported that ultrasonographies performed in experienced hands have higher degrees of accuracy comparable to MRI in the detection of myometrial invasion in cases with EC.…”
Section: Discussionsupporting
confidence: 50%
“…5,6 In our study, the presence of LN metastasis was associated significantly with the patient's age. Savelli et al reported that ultrasonographies performed in experienced hands have higher degrees of accuracy comparable to MRI in the detection of myometrial invasion in cases with EC.…”
Section: Discussionsupporting
confidence: 50%
“…Dorum et al ,[19] reported two such cases of endometrial cancer [Figures 4–5] with ET of <4 mm in their series of 100 women with PMB. Philip et al ,[20] reported in their study including 85 Jamaican women that half of the patients with endometrial carcinoma had an ET of 3–4 mm. These articles at the same time, discuss the probable reason for this disparity.…”
Section: Resultsmentioning
confidence: 99%
“…While studies have shown that a 5mm or less postmenopausal endometrial thickness is associated with benign histology in white women, this was not confirmed in an Asian population (18–21). A subsequent study of Afro-Caribbean Jamaican women with postmenopausal bleeding found that an endometrial thickness of <5mm did not exclude endometrial cancer (22). In a retrospective cohort study evaluating the predictive value of cycle characteristics for clinical pregnancy in Caucasian women after fresh embryo transfer, Traub et al (23) reported that having a thicker endometrial stripe was a positive predictor of clinical pregnancy.…”
Section: Discussionmentioning
confidence: 99%